Bilateral congenital inguinal hernia with right-sided Amyand's hernia in a premature twin: Case report and a summary of clinical presentations, management and outcomes in neonates and infants with Amyand's hernia. (November 2021) - Hernández-López, Urías De Jesús; Vargas-Buelvas, Audrey; Muñoz-Murillo, Willfrant Jhonnathan; Muñoz-Murillo, Katherine Lizeth; Nuñez-Rojas, Gian; Rahman, Sabrina
Abstract: Introduction and importance: Congenital hernias occur 70% on the right side, 25% on the left side, and approximately 5% bilaterally. The finding of a congenital Amyand's hernia is of interest, especially in patients who do not present risk factors associated with connective tissue disorders, ascitic conditions, fetal developmental disorders or any condition that increases abdominal pressure. Case presentation: Male patient, 6 months old, was brought to the pediatric surgery department due to a visible mass in the bilateral inguinal region, which protruded with crying. The parents report that he was a 36-week preterm, low birth weight, monochorionic monoamniotic twin with bilateral congenital inguinal hernia. An open herniorrhaphy was performed, showing a left communicating hydrocele with an indirect left inguinal hernia and right communicating hydrocele with indirect inguinal hernia containing cecal appendix with no signs of inflammation. Clinical discussion: The most common clinical presentation is the presence of a reducible or irreducible mass, erythema and/or inguino-scrotal edema, irritability manifested by crying and recurrent pain in older infants. This condition may be associated with cryptorchidism, intrauterine structural developmental disorder, and the presence of fistulas. Appendectomy and traditional hernia reduction are the most common surgical approach. The evolution of this condition is favorable with extremely low complication rates. Conclusion: Amyand's hernia in the neonate is a rare presenting condition, which frequently involves nearby structures with risk of inflammation, incarceration and perforation, so repair should be performed early. Highlights: Currently there are controversies in the approach of congenital inguinal hernias. The overall outcome in the management of congenital hernia is favorable. Traditional hernia management for congenital Amyand's hernia has good results.